Multiple selves, multiple voices, multiple genres: reflections in writing and art making. Issue 2 (4th March 2018) - Kawka, Marta
Abstract: In this article, I use the method of 'talking to myself' as a mode of critical reflection about the practices of art making and art writing. This 'reflective conversation' manifested the multiple voices of the dialogic self who either thwarted me or spurred me on, in the process of writing. The article presents reflection as a conflict between an authentic reflection which is true to one's sense of lived being with the requirements to fit within a particular writing genre suitable for a disciplinary tribe that may reject or support the particular method of reflection. I suggest that attending to, and critically reflecting upon, our internal dialogue and acknowledging its conflictual nature can be a sustained process of reflection where different points of view are explored, questioned, reinterpreted and reshaped. The conversation with my multiple selves is presented in the form of a play script as an authentic format to capture multiple selves interacting. In so doing, I reflect upon artistic practice and its relationship to thought, reflection and action.